Do Hiring Credits Work in Recessions? Evidence from France - Pierre Cahuc; Stéphane Carcillo; Thomas Le Barbanchon (Institute for the Study of Labor (IZA), 2014)
This paper evaluates the impact of an unexpected temporary hiring credit targeted at workers paid below 1.6 times the minimum wage in firms with less than 10 employees in France from December 2008 to December 2009. Using rich administrative data covering all French firms, we find that the program has had a strong and rapid impact on employment. The net cost per job created for the government was around zero. The employment effect was stronger in areas where recruitment was easier. Although the hiring credit was not conditional on net job creation, it did not increase churning of workers. Nevertheless, we estimate that a credit conditional on net job creation above the employment growth threshold of -1%, would have maximized job creation, and created about 4 times more jobs, at constant budget, provided that take-up had remained the same.
Keywords: C31; C93; J6; 330; labor demand; hiring credit